Germany's new top managers? The corporate elite in flux, 1960 - 2005 - Saskia Freye (Max Planck Institute for the Study of Societies, 2010)
Against the background of an observed strategic realignment of corporations in Germany towards the financial markets and the interests of shareholders, attention is also increasingly drawn to the top managers. Yet recent studies on the recruitment and career patterns of the German corporate elite present ambiguous results. While some studies suggest that career paths remain stable, others find evidence that patterns are changing. Drawing on these different results, scholars either highlight or reject a linkage between the career patterns of top managers and the realignment of corporate strategies. Against the background of these contradictory findings, this paper investigates the changing composition of the German corporate elite. It is based upon a unique dataset capturing the career paths of the CEOs of the fifty largest industrial companies in Germany for every five years between 1960 and 2005. For the first time the development of the career paths of German top managers can be analyzed over a period of 45 years. The analysis focuses on four career patterns which are commonly associated with German managers. Although these patterns appear stable at first sight, closer examination reveals substantial changes. Building on insights from the sociological management literature and economic sociology, the results of this study indicate a link between career patterns and the observed change in corporate strategies. Therefore it is argued that the changing composition of the German corporate elite may be relevant to the discussion on the unwinding of Deutschland AG, the specific corporate governance system of postwar Germany. – – Im Zusammenhang mit einer stärkeren strategischen Ausrichtung deutscher Unternehmen an den Finanzmärkten sowie den Interessen der Anteilseigner geraten Topmanager zunehmend ins Zentrum des Interesses. Bei der Analyse der Rekrutierungsmuster und Zusammensetzung der deutschen Wirtschaftselite kommen jüngste Studien zu keinem eindeutigen Ergebnis. Es ist zum einen umstritten, ob sich die Rekrutierungsmuster des Topmanagements verändert haben. Zum anderen gibt es widersprüchliche Analysen zum Zusammenhang zwischen den Rekrutierungsmustern und der strategischen Neuausrichtung von Unternehmen. Vor dem Hintergrund dieser unterschiedlichen Beurteilungen untersucht das Papier Veränderungen in der Zusammensetzung und den Rekrutierungsmustern der deutschen Wirtschaftselite. Die Grundlage dafür bildet eine Datenbank, in der die Karriereverläufe von Vorstandsvorsitzenden der deutschen Industrie zu zehn Zeitpunkten zwischen 1960 und 2005 erfasst sind. Erstmals können die Karrieremuster der Topmanager in Deutschland über einen Zeitraum von 45 Jahren analysiert werden. Untersucht werden einige Karrieremerkmale, die im internationalen Vergleich als typisch für deutsche Manager gelten. Auf den ersten Blick scheinen sich die Karriereverläufe der Manager durch hohe Kontinuität auszuzeichnen. In einer differenzierteren Analyse werden hingegen substanzielle Veränderungen sichtbar. Auf Erkenntnisse der soziologischen Managementliteratur und der Wirtschaftssoziologie aufbauend deuten die Ergebnisse der Studie auf eine Verbindung zwischen den Karrieremerkmalen der Manager und dem beobachteten Strategiewandel in der Wirtschaft hin. Vor diesem Hintergrund sollte die veränderte Zusammensetzung der deutschen Wirtschaftselite auch für die Literatur zur Auflösung der Deutschland AG von Interesse sein.
Keywords: 300